PENGETAHUAN SEBAGAI DETERMINAN KEJADIAN ANEMIA PADA IBU HAMIL - Dewi Indriani; Sefrina Rukmawati; Ike Nurrochmawati; Remita Yuli Kusumaningrum (LPPM STIKes SATRIA BHAKTI NGANJUK, 2025)
Anemia in pregnancy is one of the conditions that has a negative impact and isoften experienced by pregnant women. The incidence of anemia in Indonesia is still very high.The purpose of this research is to analyze the level of knowledge regarding the occurrence ofanemia in pregnant women in Sukorejo, Rejoso District, Nganjuk Regency